SOCIAL RESPONSIBILITY AS A STRATEGY IN BUSINESS MANAGEMENT - Silva, Ana Paula Teixeira da; Coutinho, Diogenes José Gusmão (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2023)
This paper addresses aspects of corporate social business responsibility their historical processes and theories that explain this strategy. It addresses the environmental preservation and other theories to improve the quality of life society. Likewise is discussed in the disclosure of the social enterprises and their benefits. The tools for business management ethics are essential to contemporary management. Seeking the welfare of customers, suppliers and society, thus becoming socially responsible. The new way to consume has changed the strategic vision of the companies, seeking to establish itself in the market today. Social responsibility accepts the role of an important management tool that can also result in numerous benefits to society.